Pengaruh Variasi Produk dan Store Atmosphere terhadap Kunjungan Kembali Konsumen Kilat Kuphi Jalan Garuda Kota Medan (Jurnal Manajemen Kreatif dan Inovasi, 2025)
This study aims to analyze the effect of product variation and store atmosphere on customer revisit intention at Kilat Kuphi, Jalan Garuda, Medan. A quantitative associative approach was applied by distributing questionnaires to 100 respondents, and the data were analyzed using inferential statistics with SPSS. The results show that both product variation and store atmosphere have a positive and significant influence, either partially or simultaneously, on revisit intention. Product tangibility and interior display emerged as dominant indicators in shaping positive customer experiences. These findings highlight that continuous innovation in product offerings and store atmosphere management is crucial for enhancing customer loyalty and ensuring business sustainability. Furthermore, the study emphasizes the importance of maintaining consistency in both product offerings and store ambiance to ensure that customers return. By focusing on these two key areas, businesses can foster long-term relationships with customers, increase brand loyalty, and ultimately enhance profitability. The implications of this study suggest that retailers, particularly in the competitive market of Medan, should prioritize not only product diversity but also the creation of a pleasant and immersive store environment to drive customer retention.